2020
DOI: 10.18502/ijpa.v15i1.2524
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Molecular Identification of Cryptosporidium Species among Immunocompromised Patients Referred to Hos-pitals, Central Iran, 2015-16

Abstract: Background: The purpose of this study was to determine the prevalence and genotype of Cryptosporidium spp. in different groups of immunocompromised patients admitted to the referral hospitals in center of Iran during 2015–2016. Methods: This cross-sectional study was conducted on 346 immunocompromised patients (HIV+/AIDS, Lymphoma, Leukemia and organ transplants) in referred hospitals from central parts of Iran including Isfahan, Markazi, Yazd and Chaharmahale Bakhtiari provinces. Stool samples were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Some authors report a prevalence similar to that found in this study. In a cross-sectional study conducted among 346 immunocompromised patients in Iran, the prevalence of cryptosporidiosis among HIV/AIDS patients was 4.6% and the overall prevalence in the study population was 3.5% [ 39 ]. Another study carried out in Indonesia among adult HIV/AIDS patients with chronic diarrhea and without antiretroviral therapy showed a prevalence of 4.9% [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors report a prevalence similar to that found in this study. In a cross-sectional study conducted among 346 immunocompromised patients in Iran, the prevalence of cryptosporidiosis among HIV/AIDS patients was 4.6% and the overall prevalence in the study population was 3.5% [ 39 ]. Another study carried out in Indonesia among adult HIV/AIDS patients with chronic diarrhea and without antiretroviral therapy showed a prevalence of 4.9% [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the high heterogeneity of the data found in the literature on the prevalence of cryptosporidiosis in PLHIV, there are discrepancies regarding the most common species that cause infection in this population. Most studies report C. hominis as the most prevalent species [ 13 , 36 , 39 , 51 , 52 , 53 , 54 ], while in other studies C. parvum is the most frequent [ 16 , 55 , 56 , 57 , 58 ]. This discrepancy does not appear to be associated with a geographical distribution, since both groups of reports include studies carried out on three or four continents.…”
Section: Discussionmentioning
confidence: 99%
“…For every sample, a direct microscopic examination of prepared smears applying normal saline and formalin ether concentration techniques was carried out. In addition, all slides were stained with a modified ZiehlNeelsen acid-fast method for detecting Cryptosporidium as previously described ( 12 ). To investigate the presence of Cryptosporidium oocysts, the stained slides were examined at a 100x oil immersion lens under a light microscope.…”
Section: Methodsmentioning
confidence: 99%
“…The outer forward primer: 5 ′ -GGA AGG GTT GTA TTT ATT AGA TAA AG-3 ′, the common reverse primer: Cr550 5 ′ -TGA AGG AGT AAG GAA CAA CCT CC-3 ′; which amplified an 835-bp fragment. The second step of nested-PCR was performed with an amplicon of 530 bp with the inner forward primer Cr250 5 ′ -GGA ATG AGT KRA GTA TAA ACC CC-3 ′ ( 12 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the other hand (24) in Sudan, where recorded a 27.1% infection percentage of cryptosporidium parvum infection after he collected 250 stool samples from outpatients of Kosti Hospital and used Zhel-Nielsen staining method in the parasitic diagnosis and confirmed a high prevalence among children who use water sources with pipes for drinking. ( 25) recorded a 29.6% infection rate in Peru, and the incidence rate in people with HIV was 11.5% in Isfahan35.9% in Mashhad (26) Since 2000, laboratory-confirmed cases have been reported with annual infection percentage of cryptosporidium parvum infection in Canada estimated at 35,092 (27 ) The highest incidence of Cryptosporidiosis in Canada's Arctic (28) (29) showed through studies and research on parasites to study epidemiology around the world that the prevalence of parasites varies from country to region according to the geographical difference of those countries where the spread of the parasite was 1-4% in Europe and North America while 3-30% on the continents of Africa, Asia, Australia and South and Central America (30).…”
Section: Histological Tissue Examinationmentioning
confidence: 99%